New patterns in China's rural poverty - Shi Li; Peng Zhan; Yanyang Shen (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
The purpose of this chapter is to analyze the structure of rural poverty in China. Based on data from the China Household Income Project (CHIP) in 1988, 1995, 2002, 2007, and 2013, we analyze: 1.) Anti-poverty trends and problems during the recent three decades. 2.) The structure of poverty during the recent period in comparison with previous periods. We consider those factors that may raise household income; those factors that may reduce household consumption expenditures; and other factors related to the poverty alleviation goals. We conclude that along with a reduction in the absolute poverty rate, the poverty gap increased after 2007, and the relative poverty rate continued to increase. Furthermore, according to an analysis of the reasons for poverty, we discover some positive effects of the rural social security policies on household characteristics in 2007. However, health problems among the elderly, among children below the age of 15, and among disabled adults continue to exist.
Keywords: D31; I32; P25; P36; 330; poverty structure; absolute poverty rate; relative poverty rate